Comparing the Effectiveness of Mindfulness Based Schema Therapy and Transdiagnostic Intervention on Cognitive Fusion with Illness and Posttraumatic Avoidance in Women with Breast Cancer - Fatemeh Ghayour Kazemi; Fatemeh Shahabizadeh; Maryam Safara; Soudabeh Shahidsales; Seyed Amir Aledavood; Sareh Hosseini; Ali Taghizadeh Kermani; Elham Zarei (Journal of Mazandaran University of Medical Sciences, 2023)
Background and purpose: Cancer diagnosis is a threatening and traumatic experience. Confusion caused by distressing thoughts about cancer can lead to additional suffering and, along with avoidance, can be a key factor in maintenance of traumatic reactions. The current research aimed at comparing the effectiveness of Unified Protocol (UP) of transdiagnostic intervention and mindfulness based schema therapy (MBST) on posttraumatic avoidance (PA) and chronic illness-related cognitive fusion (CICF) in patients with breast cancer (BC). Materials and methods: A semi-experimental study with pretest-posttest design and a follow-up period of 45 days was performed. Statistical population included all female patients with BC in Mashhad, Iran 2018-2021. Cognitive Fusion Questionnaire-Chronic Illness (CFQ-CI) and Posttraumatic Avoidance Scale (PAS) were administered. Forty one patients were selected using purposive sampling and were randomly divided into two experimental groups and a control group. UP of transdiagnostic intervention and MBST were applied in intervention groups for 10 weekly sessions. The control group attended two educational sessions. Data analysis was done using multivariate covariance analysis and Bonferroni post hoc test. Results: The mean scores for CICF and PA were significantly different between the intervention groups and the control group at post-test and follow-up (P<0.001). Findings showed no significant difference between the effectiveness of UP and MBST at post-test and follow-up (P>0.05). Conclusion: MBST and UP are suggested to be applied in patients with BC to reduce their psychological problems. (Clinical Trials Registry Number: IRCT20211012128050165N1)